COMPARISON OF THE USE OF SEVERAL WELLS WITH THE GASLIFT METHOD - Bekjonov Rozisher Soatmurodovich; Otamurodova Saltanat Pari Otamurodovna; Urinov Fazliddin Najmiddin ugli (American Journals Publishing, 2024)
The wellbore profile can be used for efficient use of gaslift wells as well profile for inclined wells or horizontal wells in marine conditions. In addition, it has little effect on its work even when there is high pressure and temperature in the productive layer or when there are mechanical mixtures. When there is not enough natural energy to lift the oil from the bottom of the well to the surface, the wells stop pumping. But to continue the fountain, compressed gas or air is pumped into the well with the help of NKQs. The process of gas compression is carried out using a compressor device.